SIFAT MAGNETIK DAN UKURAN PARTIKEL MAGNETIK SERTA KOMPOSISI MATERIAL PASIR BESI PANTAI KATA PARIAMAN SUMATERA BARAT DI SINTESA DENGAN IRON SAND SEPARATOR DAN BALL MILLING - Salomo salomo; Erwin Erwin; usman malik; Sandra Utama Putra (JOURNAL ONLINE OF PHYSICS, 2018)
Research on influence of Ball Milling time on magnetic properties composition and particle size of iron sand has been studied by Iron Sand Separator. The sampel was collected Kata beach Pariaman West Sumatera. Magnetic properties was studied using a solenoid wound with 2000 turns, length of 10 cm, and diameter 3 cm. Composition of the sample was studied by X-Ray Fluorescence, while particle size of the sample was studied by Particle Size Analyzer. The results showed that the size particle is 99,14 μm, 96,59 μm, and 93,34μm after processing by Ball Milling of 3, 5, and 7 hours respectively. The composition of the sample after being processed by Ball Milling of 7 hours is 12,2% and 47,387% respectively. More over, mass suseptibility of the sample increased after being processed by Ball Milling from 873,62 x 10-8 m3/Kg to 14.576,52 x 10-8 m3/Kg. These values are interval of ilmenite mineral (46 x 10-8 – 80.000 x 10-8) m3/Kg.